Induksi Kalus dan Regenerasi Tunas Padi Varietas Fatmawati - Lestari, Endang G; Yunita, Rosa (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
Efficiency of shoot regeneration from rice callus explant is an important factor, particularly for the purpose of plant genetic improvement such as somaclonal variation, transformation and in vitro selection. In the attempt of gaining shoot regeneration, callus induction and shoot regeneration experiments were conducted in the Biological Cell and Tissue Culture Laboratory, Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development. Mature seed was used as an explant. The media formulation for calli induction was MS + 2.4-D (1, 3, 5 and 7 mg/l ) + prolin (0 and 100 mg/l ) and hydrolyzed casein 3000 mg/l. The media for shoot regeneration was (1) MS + BA (1.2 and 3 mg/l ) + IAA 0.8 mg/l + prolin 100 mg/l, and (2) MS + BA 2 mg/l + IAA 0.8 mg/l + zeatin (0.1; 0.2 and 0.3 mg/l). The result showed that the embryogenic calli could be produced from MS + 2.4-D 3 mg/l + hydrolyzed casein 3000 mg/l treatment and the best media for shoot induction was MS + BA 2 mg/l + IAA 0.8 mg/l + zeatin 0.2 mg/l. The obtained plantlets were successfully acclimatized in the greenhouse.